Jump Hurdlers: an Adventure game based on 2D using Gdevelop 5 - Tawakal, Rayendra; Eldo, Handry; Ramadan, Rifqi (Department of Informatics Faculty of Engineering Universitas Malikussaleh, 2024)
The more advanced technological developments in this modern era are, the more new games emerge with graphic quality that is closer to real life. The newest games which make the game graphics more real are indeed increasingly interesting and make the players switch to these more modern games and start to forget. 2-dimensional games that are flat or flat are only 2 dimensions. The 2-dimensional games that used to be a favorite in the 90s are starting to be abandoned, so this 2-dimensional based adventure game has been brought back to popularize the less interesting 2-dimensional based games into 2-dimensional games with a more modern appearance and graphic design with a flat design as the base. so that games like this will develop in the modern market and can compete with 3-dimensional based games. Adventure games can also be said to be games that give players the opportunity to analyze the game arena visually. This game also does not require players to have special abilities in completing a mission, but simply by defeating enemies, avoiding obstacles, and following the storyline in a game. game.